Et sheava nafshi - Alexander, Ilil (Israel : Rofekamp, Jan, 2004)
With moving intimacy, "Keep Not Silent" documents the lives of three Ortho-Dykes, lesbians living, with varying degrees of anonymity, within the Orthodox population of Jerusalem. Miriam-Esther is married and keeps her desires completely hidden from her husband and children; Ruth lives a double life, alternating nights between her girlfriend and her completely aware husband; and Yehudit lives openly with her partner despite her rabbi father’s disapproval. Though Yehudit is the only one to allow her face to be shown, each woman nevertheless displays immense courage by speaking out on camera at all, with so much to risk.
Duration: 00:52:00
Keywords: Documentary films